2019
DOI: 10.1155/2019/7148032
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Provides Effective Immunosuppression for Improved Survival of Retinal Organoids after Epiretinal Transplantation

Abstract: We investigated the efficacy of the immunosuppressants rapamycin (RAP) and dexamethasone (DEX) in improving the survival of retinal organoids after epiretinal transplantation. We first compared the immunosuppressive abilities of DEX and RAP in activated microglia in an in vitro setting. Following this, we used immunofluorescence, real-time polymerase chain reaction, and flow cytometry to investigate the effects of DEX and RAP on cells in the retinal organoids. Retinal organoids were then seeded onto poly(lacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Dexamethasone (DEX), a synthetic corticosteroid, is a clinical immunosuppressant. Evidence has indicated that DEX improves the survival of retinal organoids 63 .…”
Section: Construction Of Pdosmentioning
confidence: 99%
“…Dexamethasone (DEX), a synthetic corticosteroid, is a clinical immunosuppressant. Evidence has indicated that DEX improves the survival of retinal organoids 63 .…”
Section: Construction Of Pdosmentioning
confidence: 99%
“…Xian et al seeded 'retinas' from organoids onto Poly(Lactic-co-Glycolic) Acid (PLGA) scaffolds and implanted them into rhesus monkey eyes, some with Chronic Ocular Hypertension (OHT) induction. The survival and differentiation of these 'retinas' in OHT eyes were successful only with the DEX treatment, indicating that DEX is likely a promising immunosuppressant to enhance the survival of epiretinal implants [108].…”
Section: Transplantation Of Retinal Sheets In Animal Models and Humanmentioning
confidence: 99%